Obstetric imaging - Copel, Joshua A. (Expert radiology series., 2012)
Obstetric Imaging will help you detect fetal abnormalities with greater confidence and accuracy. Covering MRI as well as ultrasound and interventional procedures, it equips you with expert tips for recognizing and addressing problems that you might otherwise miss. Obstetric Imaging provides the advanced guidance you need to recognize fetal health challenges early and respond effectively.